PENGARUH INTENSITAS PENGGUNAAN SMARTPHONE TERHADAP SOSIAL EMOSIONAL ANAK USIA DINI (5-6 TAHUN) DI TK NEGERI PEMBINA MALIN DEMAN - Freti Sahani; Nelly Marhayati; Dita Lestari (Al Fitrah: Journal Of Early Childhood Islamic Education, 2026)
The use of smartphones among early childhood has increased and is assumed to affect children's social-emotional development. Therefore, this study aimed to de-termine the effect of smartphone use intensity on the social-emotional development of children aged 5–6 years at TK Negeri Pembina Malin Deman. This study em-ployed a quantitative method with an associative approach. The research subjects consisted of 74 parents, including 37 fathers and 37 mothers. Data were collected through observation, questionnaires, and documentation. Data analysis was con-ducted using SPSS through classical assumption tests, including normality and lin-earity tests, followed by simple linear regression analysis to test the research hy-pothesis. The results showed that there was a significant effect of smartphone use intensity on the social-emotional development of children aged 5–6 years at TK Negeri Pembina Malin Deman. Based on the mothers' data, the significance value was < 0.001 < 0.05 with a coefficient of determination of 0.528 or 52.8%, while based on the fathers' data, the significance value was 0.002 < 0.05 with a coeffi-cient of determination of 0.245 or 24.5%. These findings indicate that smartphone use intensity has an effect on children's social-emotional development, while the remaining variance is influenced by other factors outside this study.